1971
DOI: 10.1002/bjs.1800580604
|View full text |Cite
|
Sign up to set email alerts
|

The injuries and management of riot casualties admitted to the belfast hospital wards, August to October, 1969

Abstract: Belfast has experienced intermittent rioting for 18 months. An analysis of riot casualties admitted to the wards of Belfast hospitals from 1 Aug. to 31 Oct., 1969, is presented. Approximately 500 casualties came to hospital and of these only 164 were admitted. Eighty‐three (50·6 per cent of admissions) required surgery. One‐third of all admissions had left hospital within 48 hours and only 23 (14 per cent) remained for longer than 2 weeks. The demand for resuscitation was not high and the need for blood unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The studies showed that the majority of the injuries in civil riots involved the head (12.6%-40.7%) and limbs (33.1%-81.9%). (2)(3)(4)(5) This is similar to our study, in which most of the injuries were to the head (50.0%) and limbs (38.9%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The studies showed that the majority of the injuries in civil riots involved the head (12.6%-40.7%) and limbs (33.1%-81.9%). (2)(3)(4)(5) This is similar to our study, in which most of the injuries were to the head (50.0%) and limbs (38.9%).…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to other studies, whereby most casualties could be managed as outpatients (55.9%-67.2%). (2,4) The patient who was admitted underwent computed tomography of the head, which did not show any intracranial bleeding. He was observed in the ED short stay unit and subsequently discharged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Civilian surgeons faced with weapon casualties may make decisions on the surgical management of wounds (Robb and Matthews 1971) which are at variance with those of civilian surgeons in battlefield situations (Dudley et al 1968) or with those made by military surgeons (Moffat 1967, O'Brien 1973.…”
Section: Surgical Treatment Of Woundsmentioning
confidence: 99%